Fetal Congenital Peripheral Bronchial Atresia Diagnosed by Magnetic Resonance Imaging: Two Case Reports - Kozaki, Mitsuru; Iraha, Yuko; Masamoto, Hitoshi; Nitta, Hayase; Chinen, Yukiko; Kinjo, Tadatsugu; Mekaru, Keiko; Aoki, Yoichi (American Journal of Perinatology Reports, 2018)
Two types of congenital bronchial atresia (proximal and peripheral) have been classified. We report two cases of peripheral bronchial atresia diagnosed by prenatal ultrasonography (US) and magnetic resonance imaging (MRI). Evaluating an enlarged lung mass that is homogeneously hyperechoic on US and hyperintense on T2-weighted MRI can help in determining whether bronchial atresia is present. Proximal type is suggested when a dilated main bronchus is observed as a tubule structure of an involved lung hilum. In our cases, T2-weighted MRI revealed homogeneously hyperintense lung lesion with decreased signal intensity of adjacent lobe, flattening diaphragm, and mediastinal shift. Dilatation of the main bronchus was not observed and the opposite lung was normal in appearance. These findings were explained by secondary compression due to enlargement of the involved lung. The preservation of vascular structure and the retained normal shape, though enlarged, in the affected lobe were observed, which demonstrated undisrupted pulmonary architecture of the lobe. Thus, congenital cystic adenomatoid malformation was excluded because pulmonary architecture was relatively preserved. Finally, presumed diagnoses of the peripheral bronchial atresia were made and confirmed by postnatal chest computed tomography.
Keywords: congenital bronchial atresia; prenatal diagnosis; magnetic resonance imaging; ultrasonography